2014
DOI: 10.9755/ejfa.v26i4.17664
|View full text |Cite
|
Sign up to set email alerts
|

Impact of husbandry, stages of lactation and parity number on milk yield and chemical composition of dromedary camel milk

Abstract: The present study was designed to assess the impact of husbandry, stage of lactation and parity number on milk yield and chemical composition of camel milk within three different camel farms at Khartoum State, Sudan. Camel milk samples (n=220) were collected from 43 healthy she-camels at different lactation stages (early, mid, late and latest stages of lactation) and parity number (1-7 parities). The overall means of daily milk yield and composition of fat, protein, lactose, solids not fat (SNF), acidity and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…Sheep milk is rich in casein and whey proteins 4.2–5.2 g/100 g and 1.02–1.3 g/100 g respectively ( Barros et al., 2017 ; Selvaggi et al, 2015 ; Selvaggi et al, 2017 ) and protein content in camel milk was between 2.15%–4.90% ( Al Kanhal and AL haj, 2010 ). The current results of casein and whey proteins in camel milk are also similar with the findings of other researchers ( Babiker and El-Zubeir, 2014 ; El-Agamy et al, 2009 ; Khaskheli et al, 2005 ; Musaad et al, 2013 ).…”
Section: Resultssupporting
confidence: 93%
“…Sheep milk is rich in casein and whey proteins 4.2–5.2 g/100 g and 1.02–1.3 g/100 g respectively ( Barros et al., 2017 ; Selvaggi et al, 2015 ; Selvaggi et al, 2017 ) and protein content in camel milk was between 2.15%–4.90% ( Al Kanhal and AL haj, 2010 ). The current results of casein and whey proteins in camel milk are also similar with the findings of other researchers ( Babiker and El-Zubeir, 2014 ; El-Agamy et al, 2009 ; Khaskheli et al, 2005 ; Musaad et al, 2013 ).…”
Section: Resultssupporting
confidence: 93%
“…In agreement with previous studies, lactose content of our study significantly decreased from early to late lactation stages (Ahmad et al, 2012;Aljumaah et al, 2012;Babiker and El-Zubeir, 2014;Nagy et al, 2017). The low THI class (December to March) of our study recorded the highest and significant fat and protein percentages, while the high THI class (July-August) recorded the lowest values.…”
Section: Discussionsupporting
confidence: 92%
“…Our results were in agreement with those reported by Mestawet et al (2012), who reported higher fat and TS at the late stage of lactation. On the contrary, Zeleke (2007), Aljumaah et al (2012) and Babiker and El-Zubeir (2014) reported the highest fat content during the first three months of lactation. Moreover, recorded a non-significant effect of lactation stage on fat and TS contents among pastoral herders grazing on natural vegetation.…”
Section: Discussionmentioning
confidence: 95%
“…El Zubeir and Ibrahium (2009) reported variations in developed acidity and the pH for Garris made with pasteurized and non pasteurized milk. Moreover, the variation in the chemical composition of camel milk could be due to other reasons such as the management, locations and environment (Zeleke, 2007;Bakheit et al, 2008;Shuiep et al, 2008;Dowelmadina et al, 2014;Babiker and El Zubeir, 2014. ) and processing conditions (Hassan et al, 2007 andEl Zubeir andIbrahium, 2009).…”
Section: Discussionmentioning
confidence: 99%